Multi-walled carbon nanotube-induced genotoxic, inflammatory and pro-fibrotic responses in mice: Investigating the mechanisms of pulmonary carcinogenesis - Rahman, Luna; Jacobsen, Nicklas Raun; Aziz, Syed Abdul; Wu, Dongmei; Williams, Andrew; Yauk, Carole L.; White, Paul; Wallin, Hakan; Vogel, Ulla; Halappanavar, Sabina (Mutation research, 2017)
•The lung responses of straight and rigid MWCNTs, NM-401 and Mitsui-7 were tested.•Genotoxic, inflammatory, fibrotic and gene expression responses were investigated.•Both MWCNTs induce low levels of DNA breaks, p53 activation, but are not mutagenic.•Both MWCNTs perturb expression of inflammatory, fibrotic and cancer genes in lung.•MWCNT-induced carcinogenic mechanisms may involve more than just the genotoxicity. The International Agency for Research on Cancer has classified one type of multi-walled carbon nanotubes (MWCNTs) as possibly carcinogenic to humans. However, the underlying mechanisms of MWCNT- induced carcinogenicity are not known. In this study, the genotoxic, mutagenic, inflammatory, and fibrotic potential of MWCNTs were investigated. Muta™Mouse adult females were exposed to 36±6 or 109±18μg/mouse of Mitsui-7, or 26±2 or 78±5μg/mouse of NM-401, once a week for four consecutive weeks via intratracheal instillations, alongside vehicle-treated controls. Samples were collected 90days following the first exposure for measurement of DNA strand breaks, lacZ mutant frequency, p53 expression, cell proliferation, lung inflammation, histopathology, and changes in global gene expression. Both MWCNT types persisted in lung tissues 90days post-exposure, and induced lung inflammation and fibrosis to similar extents. However, there was no evidence of DNA damage as measured by the comet assay following Mitsui-7 exposure, or increases in lacZ mutant frequency, for either MWCNTs. Increased p53 expression was observed in the fibrotic foci induced by both MWCNTs. Gene expression analysis revealed perturbations of a number of biological processes associated with cancer including cell death, cell proliferation, free radical scavenging, and others in both groups, with the largest response in NM-401-treated mice. The results suggest that if the two MWCNT types were capable of inducing DNA damage, strong adaptive responses mounted against the damage, resulting in efficient and timely elimination of damaged cells through cell death, may have prevented accumulation of DNA damage and mutations at the post-exposure time point investigated in the study. Thus, MWCNT-induced carcinogenesis may involve ongoing low levels of DNA damage in an environment of persisting fibres, chronic inflammation and tissue irritation, and parallel increases or decreases in the expression of genes involved in several pro-carcinogenic pathways.